2017
DOI: 10.4103/iju.iju_8_17
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted retroperitoneal lymph node dissection: Feasibility and outcome in postchemotherapy residual mass in testicular cancer

Abstract: Introduction:We aimed to evaluate the surgical feasibility, complication, and oncological outcome of robot-assisted retroperitoneal lymph node dissection (RA-RPLND) in patients of testicular tumor with postchemotherapy residual retroperitoneal mass.Methods:A total of 13 patients underwent RA-RPLND between January 2012 and September 2016 at our institute. A study was started on December 2015, so data were collected retrospectively and prospectively regarding patient demography, tumor characteristics, surgical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…In the largest series of 47 patients (all chemotherapy naïve), Pearce et al [89] performed R-RPLND in 42 patients with clinical Stage I disease. Although R-RPLND in post-chemotherapy patients has been described, this is only in 37 of the 126 reported cases [86] , [87] , [88] , [89] , [90] , [91] . The preference to perform R-RPLND in chemo-naïve clinical Stage I patients is not consistent with contemporary practice [93] .…”
Section: Robot-assisted Retroperitoneal Lymph Node Dissection (R-rplnmentioning
confidence: 98%
See 1 more Smart Citation
“…In the largest series of 47 patients (all chemotherapy naïve), Pearce et al [89] performed R-RPLND in 42 patients with clinical Stage I disease. Although R-RPLND in post-chemotherapy patients has been described, this is only in 37 of the 126 reported cases [86] , [87] , [88] , [89] , [90] , [91] . The preference to perform R-RPLND in chemo-naïve clinical Stage I patients is not consistent with contemporary practice [93] .…”
Section: Robot-assisted Retroperitoneal Lymph Node Dissection (R-rplnmentioning
confidence: 98%
“…Two of these case series were in less than three patients. Data summarised from the remaining six larger case series are presented in Table 6 [86] , [87] , [88] , [89] , [90] , [91] .…”
Section: Robot-assisted Retroperitoneal Lymph Node Dissection (R-rplnmentioning
confidence: 99%
“…Retroperitoneal lymph node dissection is recommended for residual masses after chemotherapy for nonseminomatous germ cell tumors since germ cell tumor elements may persist in about 50% of patients. Singh and co-workers[ 2 ] report their experience with robotic retroperitoneal lymphadenectomy in a series of 13 such men. They report a median yield of 20 lymph nodes.…”
Section: Robotic Retroperitoneal Lymphadenectomy For Postchemotherapymentioning
confidence: 99%
“…During the past decade, many studies have suggested that the metabolic fate of pyruvate is regulated by tyrosine phosphorylation. [35] Vitamin A plays an important role in cell signaling. Abnormal retinoid signaling in the cytoplasm and nucleus has been reported in human cancers.…”
Section: Introductionmentioning
confidence: 99%